FV 3. Diagnostic value of oculomotor parameters in progressive supranuclear palsy: a monocentric study in 100 patients. Issue 8 (August 2021) - Wunderlich, J.; Behler, A.; Ludolph, A.C.; Pinkhardt, E.H.; Kassubek, J.
Abstract : Introduction . For progressive supranuclear palsy (PSP), oculomotor function is one of the core features on which the diagnosis is based upon according to the diagnostic criteria by the Movement Disorder Society (MDS) supported PSP-Study-Group from 2017 ("O criterion"). The aim of this study was to analyze the value of specific oculomotor parameters. Material/Method. An analysis of the videooculographic examinations of smooth pursuit eye movements and visually guided reactive saccades in 100 PSP patients and 49 matched control subjects was performed. Group differences as well as correlations were tested at a two-sided level α=0.05. Cut-off values for the development of new subgroups were defined by the fifth or 95th percentile of specific parameters of the control group. ROC-analyses were used to determine sensitivity and specificity. Results. Each of the investigated oculomotor parameters (for smooth pursuit eye movements gain, for saccades latency, gain, peak eye velocity, asymmetry of velocities up- and downwards, rate of saccadic intrusions (SI)) was significantly altered in PSP compared with the control population (p<0.0001 each). The threshold for vertical saccade velocity was approximately 240°/s for both components so that about 70% of the patients could be captured. A cut-off value of 9.60°/s was determined for SI, and approximately 56% of the patients achieved higher values. By combining both parameters, almost 80% of the patients could be classified. With regard to the specifically calculated asymmetry of the vertical saccade velocities, 34% of the patients were abnormal at a threshold of 0.42 (overview in Fig. 1). The majority of patients (63.5%) performed faster downward than upward saccades. The vertical saccade velocity and SI had a high specificity of more than 95%, while sensitivity was maximally 60% for the velocity components and 54.2% for the SI. At similar specificity, the asymmetry reached a sensitivity of 27.1%. Discussion . The results for vertical saccade velocity and SI, respectively, emphasized their relevance as part of the MDS-PSP diagnostic criteria, whereas the significance of the asymmetry of the vertical velocities was limited. With respect to directional tendency, the findings are still heterogeneous. In future evaluations, unbiased quantifications of clinical parameters offer a good possibility to further develop the quality of the diagnostic procedures used for PSP. Fig. 1.